2019
DOI: 10.1093/zoolinnean/zlz138
|View full text |Cite
|
Sign up to set email alerts
|

The out-of-India hypothesis: evidence from an ancient centipede genus, Rhysida (Chilopoda: Scolopendromorpha) from the Oriental Region, and systematics of Indian species

Abstract: The Oriental Region has been a focus of biogeographical research for more than two centuries. We examined systematics and biogeography of the centipede genus Rhysida in this region. A robust species hypothesis for the Indian subcontinental and Southeast Asian Rhysida clade uses molecular, morphological and distribution data. Twelve species are recognized in two monophyletic species complexes, eight belonging to the Rhysida immarginata and four to the Rhysida longipes species complex. They include Rhysida aspin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Estimates surrounding the timing of the collision between the Indian Subcontinent and Asia vary, but most studies agree on a late Paleocene/early Eocene timescale around 55 Ma ( Hu et al, 2016 ; Zheng & Wu, 2018 ; Westerweel et al, 2019 ). Migrations from the Indian Subcontinent to Asia are known to have played a significant role in generating the high faunal diversity observed in Asia today ( Karanth, 2006 ; Morley et al, 2016 ; Morley, 2018 ; Garg & Biju, 2019 ), even amongst spiders ( Li, Shao & Li, 2020 ) and other invertebrates ( Joshi, Karanth & Edgecombe, 2020 ). It has also been shown that other spiders of a comparable age originated on the Gondwanan supercontinent, i.e., South America and Africa, before eventually colonizing Asia and Oceania ( Chamberland et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates surrounding the timing of the collision between the Indian Subcontinent and Asia vary, but most studies agree on a late Paleocene/early Eocene timescale around 55 Ma ( Hu et al, 2016 ; Zheng & Wu, 2018 ; Westerweel et al, 2019 ). Migrations from the Indian Subcontinent to Asia are known to have played a significant role in generating the high faunal diversity observed in Asia today ( Karanth, 2006 ; Morley et al, 2016 ; Morley, 2018 ; Garg & Biju, 2019 ), even amongst spiders ( Li, Shao & Li, 2020 ) and other invertebrates ( Joshi, Karanth & Edgecombe, 2020 ). It has also been shown that other spiders of a comparable age originated on the Gondwanan supercontinent, i.e., South America and Africa, before eventually colonizing Asia and Oceania ( Chamberland et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primary location data (n = 100) for 19 species in the three genera of the centipede family Scolopendridae (Subfamily Otostigminae): Digitipes Attems, 1930, Ethmostigmus Pocock, 1898 and Rhysida Wood, 1862 were obtained by systematic sampling across the Western Ghats (WG) from 2008 to 2010, spanning its latitudinal and elevational gradients (Joshi et al, 2020;Joshi & Edgecombe, 2013Joshi & Karanth, 2012) (see Appendix S1 in Supporting Information). These data were supplemented with opportunistic sampling which continued to 2018.…”
Section: Species Distribution Modelsmentioning
confidence: 99%
“…Since it is challenging to identify centipede species in the field, specimens associated with the primary location data were collected and identified in the lab based on microscopic examination of morphological characters. Species identity was also assessed through molecular phylogenetic and species delimitation analyses (Joshi et al, 2020;Joshi & Edgecombe, 2013Joshi & Karanth, 2012). State forest department permits were obtained to collect centipedes in protected areas and specimens were preserved in 70% ethanol.…”
Section: Species Distribution Modelsmentioning
confidence: 99%
See 2 more Smart Citations